The effects of amoxicillin with or without clavulanic acid on the postoperative complaints after third molar surgery: a retrospective chart analysis - Esen, Alparslan (J Istanb Univ Fac Dent, 2017)
PURPOSE: The aim of this chart-based retrospective study was to evaluate the effects of orally administered amoxicillin alone or amoxicillin combined with clavulanic acid on the frequency of post-operative complications and patients’ comfort after mandibular third molar surgery. MATERIALS AND METHODS: The records of patients who had undergone lower third molar surgery between October 2014 and December 2015 were examined. A total of 62 patients who had fully impacted teeth in mesioangular position and who had been prescribed same type and dose of anti-inflammatory drug were included in this study. Among them, 32 subjects were found to have been prescribed 500 mg amoxicillin trihydrate orally every 8 h for 5 days (Group A) and 30 patients 500 mg amoxicillin trihydrate plus 125 mg potassium clavulanate orally every 8 h for 5 days postoperatively (Group AC). Post-operative pain levels, swelling, presence of trismus, frequency of alveolar osteitis and quality of life (QoL) scores were gathered from patients’ charts and were statistically compared. RESULTS: Analysis of the variables showed that there were no significant differences between the Groups A and AC regarding pain levels, swelling, trismus and QoL scores. The frequency of alveolar osteitis was found to be 1.6% in the Group A, however, no significant difference was observed among study groups. CONCLUSION: Within the limitations of this retrospective chart review, it can be stated that amoxicillin and amoxicillin with clavulanic acid might provide similar outcome in terms of patient comfort following third molar surgery.